High Power In-Plane Micro-Supercapacitors Based on Mesoporous Polyaniline Patterned Graphene - Liu, Zhaoyang; Liu, Shaohua; Dong, Renhao; Yang, Sheng; Lu, Hao; Narita, Akimitsu; Feng, Xinliang; Muellen, Klaus (Small, 2017)
Researchers reported micro-supercapacitors (MSCs) based on mesoporous polyaniline (mPANi) patterned graphene, by combining pseudocapacitive mPANi and electron-double-layer-capacitive graphene, to tackle the current rate capability challenge of MSCs. They produced graphene sheets by electrochemical exfoliation of graphite, which is a promising wet-chemical method with advantages including high quality of graphene and solution processability, as well as up-scalability and eco-friendliness, in contrast to liquid-phase exfoliation in organic solvents. The fabricated MSCs offered a significant volumetric capacitance as high as 75 F cm-3 at 10 mV s-1, and exhibited an excellent rate capability with capacitance retention of 16% when operated from 10 to 105 mV s-1.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electrochemically exfoliated graphene; energy storage; high power; mesoporous polyaniline; micro-supercapacitors